Gene for the alpha subunit of Bacillus subtilis RNA polymerase maps in the ribosomal protein gene cluster. - Suh, J W (1986)
We isolated the gene encoding the alpha subunit of Bacillus subtilis RNA polymerase from a lambda gt11 expression vector library by using anti-alpha antibody as a probe. Four unique clones were isolated, one carrying a lacZ-alpha gene fusion and three carrying the entire alpha coding region together with additional sequences upstream. The identity of the cloned alpha gene was confirmed by the size and immunological reactivity of its product expressed in Escherichia coli. Further, a partial DNA sequence found the predicted NH2 terminus of alpha homologous with E. coli alpha. By plasmid integration and PBS1 transduction, we mapped alpha near rpsE and within the major ribosomal protein gene cluster on the B. subtilis chromosome. Additional DNA sequencing identified rpsM (encoding S13) and rpsK (encoding S11) upstream of alpha, followed by a 180-base-pair intercistronic region that may contain two alpha promoters. Although the organization of the alpha region resembles that of the alpha operon of E. coli, the putative promoters and absence of rpsD (encoding S4) immediately preceding the B. subtilis alpha gene suggest a different regulation.